PEMBELAJARAN MENGGEMBIRAKAN MELALUI PENDEKATAN TECHNOLOGICAL PEDAGOGICAL CONTENT KNOWLADGE - Rochsun; Sunuyeko, Nurcholis; Wijayanti, Rina (Prismatika: Jurnal Pendidikan dan Riset Matematika, 2023)
Higher-order thinking skills in 21st century learning are a requirement, so that students are able to think critically, creatively, collaboratively and communicatively. Focusing on these demands, often the learning process ignores the basic needs of students, namely happiness. Kebudiutamaan course is one of the institutional courses that must be taken by students of all study programs at IKIP Budi Utomo Malang. As with other study programs, students of the Mathematics Education Study Program also take this course. Regarding the basic needs of students, namely being happy, in taking the Virtue Course, Mathematics Education students also need fun learning. The Technological Pedagogical Content Knowledge (TPACK) approach is intended to create fun learning in the learning activities of the Civics course. This study used quantitative approach with survey data (primary) with a cross-sectional design. The sampling technique used porpusive sampling. Data collection used self-administered questionaires. The results of the non-parametric statistical test Chi-square test (χ2) with a significance level of 5%, show that there is a significant difference in the number of students of the Mathematics Education Study Program in the Kebudiutamaan subject. Students are happy with learning TPACK Plus than those who are not, and there is an increase in critical thinking skills, creative, communicative and able to work collaboratively, which is shown by the product of high-quality material content in the form of short videos.